AB0969 COMPARISON AMONG ACR1997, SLICC AND THE NEW EULAR/ACR CLASSIFICATION CRITERIA IN CHILDHOOD-ONSET SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Fonseca, Adriana; Rodrigues, Marta; Sztajnbok, Flávio R.; Land, Marcelo; Oliveira, Sheila Knupp DE
Abstract : Background: To date there are no specific classification criteria for childhood-onset systemic lupus erythematosus (cSLE). Objectives: This study aims to compare the performance among the American College of Rheumatology (ACR) 1997, the Systemic Lupus International Collaborating Clinics criteria (SLICC) and the new European League Against Rheumatism (EULAR)/ACR criteria, in a cSLE cohort. Methods: Data were retrospectively collected from medical charts of cSLE cases and controls with defined rheumatic diseases, both ANA positive, to establish each ACR1997, SLICC and EULAR/ACR criterion fulfilled, at first visit and 1-year-follow-up. Results: 122 cSLE cases and 89 controls were included. At first visit, SLICC criteria had greater sensitivity than ACR 1997 (89.3% versus 70.5%, p < 0.001), but similar specificity (80.9% versus 83.2%, p = 0.791), however performance was not statistically different at 1-year-follow-up. SLICC performed better in specificity compared to EULAR/ACR score ≥ 10 at first visit (80.9% versus 67.4%, p = 0.008) and 1-year (76.4% versus 58.4%, p = 0.001), although sensitivities were similar at both times. EULAR/ACR criteria score ≥10 exhibited greater sensitivity than ACR 1997 (87.7% versus 70.5%, p < 0.001) at first visit, but comparable at 1-year, whereas specificity was lower at first visit (67.4% versus 83.2%, p = 0.004) and 1-year (58.4% versus 76.4%, p = 0.002). A EULAR/ACR score ≥13 against a score ≥10, resulted in higher specificity, positive predictive value, and cut-off point accuracy. Compared to SLICC, a EULAR/ACR score ≥ 13 resulted in lower sensitivity at first visit (76.2% versus 89.3%, p < 0.001) and 1-year (91% versus 97.5%, p = 0.008), but similar specificities at both periods. When compared to ACR 1997, a EULAR/ACR total score ≥ 13, resulted in no differences in sensitivity and specificity at both times. Conclusion: In this cSLE population, SLICC criteria performed best at first visit and 1-year-follow-up. The adoption of a EULAR/ACR total score ≥ 13, against the initially proposed ≥10 score, was most appropriate to classify cSLE in our study. Further studies are necessary to address if SLICC might allow cSLE classification earlier in disease course and be more inclusive of cSLE subjects for clinical studies. References: [1] Tedeschi SK, Johnson SR, Boumpas DA, Daikh D, Dörner T, Jayne D, et al. Developing and Refining New Candidate Criteria for SLE Classification: An International Collaboration. Arthritis Care Res (Hoboken)2018; 70:571-581. [2] Leuchten N, Hoyer A, Brinks R, Schoels M, Schneider M, Smolen J, et al. Performance of Anti-nuclear Antibodies for Classifying Systemic Lupus Erythematosus: a Systematic Literature Review and Meta-regression of Diagnostic Data. Arthritis Care Res (Hoboken)2018; 70:428-438. [3] Aringer M, Costenbader KH, Brinks R, Boumpas D, Daikh D, Jayne D, et al. Validation of New Systemic Lupus Erythematosus Classification Criteria. In: 2018 ACR/AHRP Annual Meeting; Chicago, Illinois, 20-24 October 2018. https://acrabstracts.org. Accessed 24 Oct 2018. Disclosure of Interests: None declared